Selecting the Mercury Seven The Search for America's First Astronauts - Burgess, Colin (Space Exploration,, 2011)
In January 1959, after an exhaustive search through military service records, a number of Americas elite test pilots received orders to attend a series of top-secret briefings in Washington, D.C. These briefings were designed to assist in selecting a group of astronauts for the newly formed National Aeronautics and Space Administration (NASA) and its man-in-space program, Project Mercury. Following in-depth medical and psychological screening, 32 finalists were chosen. They would be subjected to the most rigorous, exploratory, and even degrading medical and psychological stress tests ever imposed on the nation's service personnel. NASA wanted the best of the best in its quest for the nation's first astronauts, and this is the story of that search for a group of near-supermen who were destined to become trailblazing pioneers of American space flight. For the very first time, after extensive research and numerous interviews, the names and amazing stories of those 32 finalists are finally revealed in this book. Only seven of them would ultimately be selected as America's Mercury astronauts, but those responsible for choosing the seven openly concede that it was an incredibly difficult task. They reveal that any of these courageous and superbly talented test pilots could so easily have been selected to fly into space, finding adventure, fame, and lasting renown as one of NASA's legendary Mercury astronauts.